2018
DOI: 10.14245/ns.1836128.064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognostic Factors in Patients With Myelopathy Caused by Thoracic Ossification of the Ligamentum Flavum

Abstract: ObjectiveThe objective of this study was to investigate the surgical outcomes and prognostic factors for thoracic ossification of the ligamentum flavum (OLF) after decompressive laminectomy, focusing on the quantitative signal intensity ratio (SIR) of preoperative magnetic resonance imaging (MRI) and its prognostic significance. MethodsWe retrospectively reviewed 24 patients who previously underwent total laminectomy to remove OLF from 2010 to 2015. MRI and computed tomography were performed to detect OLF. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Several studies have reported that some factors might affect the surgical results of OLF, including the duration of preoperative symptoms, preoperative neurological status, intramedullary signal changes in T2WI, age, sex, type of OLF, and dural tears 3,7,20,27,30,[35][36][37] . However, it is still uncertain whether these factors are predictive of the surgical results following MIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that some factors might affect the surgical results of OLF, including the duration of preoperative symptoms, preoperative neurological status, intramedullary signal changes in T2WI, age, sex, type of OLF, and dural tears 3,7,20,27,30,[35][36][37] . However, it is still uncertain whether these factors are predictive of the surgical results following MIS.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of myelopathy before surgery, which is mostly indicated by the preoperative mJOA score, was shown to be the most important predictor of surgical results in many studies 3,24,36,38,[41][42][43] . However, few studies found a significant correlation between the preoperative mJOA score and RR according to multiple regression analysis 3,36,41 , and one study even showed no significant correlation between them in the univariate analysis 1 . Of note, we did not find a significant correlation between the preoperative mJOA score and RR in multiple regression analysis, similar to some studies 24,29,38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the surgical outcome of patients with beak type OPLL was not poor. Many authors thought that intramedullary high signal intensity in MR image is evidence of pathologic damage to the spinal cord 11) . The pathology is considered range from acute edema to chronic myelomalacia 1,9,22) .…”
Section: Discussionmentioning
confidence: 99%
“…The number of spine surgeries has been increasing with the development of diagnostic modalities, improved surgical techniques, increased options for minimally invasive surgeries and increased number of patients with spinal disease [27]. LF is an important anatomical barrier for prevention of postoperative scar tissue [5,12,13,28,29] and mechanical stabilization of the lumbar segment [30,31]. Because most patients with LDH do not have spinal instability, preservation of LF may be beneficial considering long-term stability of the lumbar spinal segment and prevention of postoperative adhesions.…”
Section: Discussionmentioning
confidence: 99%